2016
DOI: 10.3892/mco.2016.866
|View full text |Cite
|
Sign up to set email alerts
|

Durable response to lenalidomide in a patient with myelodysplastic syndrome associated with isolated 5q deletion and JAK2 V617F mutation despite discontinuation of treatment

Abstract: Abstract. Loss of a section of the long arm of chromosome 5, as a sole cytogenetic abnormality, characterizes a rare type of myelodysplastic syndrome [del(5q) MDS] and the co-existence of the JAK2 V617F mutation occurs in a small subset of these cases. Patients with isolated del(5q) MDS have a relatively favorable prognosis, with transformation to acute myeloid leukemia occurring in <10%, and their disease responds well to lenalidomide. However the optimal therapeutic approach for patients with del(5q) MDS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…As previously reported in patients with a concomitant del(5q) and JAK2 V617F mutation, the hallmark of our patients' presentations include anemia and marked thrombocytosis [10]. A majority of patients are also transfusion dependent [10,13,14]. While this appears similar to MPNs, the transfusion-dependent anemia and thrombocytosis does not typically respond to erythropoietin and hydroxyurea respectively [14][15][16].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…As previously reported in patients with a concomitant del(5q) and JAK2 V617F mutation, the hallmark of our patients' presentations include anemia and marked thrombocytosis [10]. A majority of patients are also transfusion dependent [10,13,14]. While this appears similar to MPNs, the transfusion-dependent anemia and thrombocytosis does not typically respond to erythropoietin and hydroxyurea respectively [14][15][16].…”
Section: Discussionsupporting
confidence: 52%
“…While this appears similar to MPNs, the transfusion-dependent anemia and thrombocytosis does not typically respond to erythropoietin and hydroxyurea respectively [14][15][16]. In some cases with a del (5q) and JAK2 V617F mutation, platelet and leukocyte counts did normalize with a regimen of interferon-alpha, aspirin and hydroxyurea, but this did not improve the anemia [10,13]. This behavior, as well as the response to lenalidomide, is more similar to an MDS-type clinical course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some retrospective case reports or series involving a small number of patients have shown that most RBC-TI patients who stopped LEN maintained the hematological response. This nding was more evident in patients who had received at least 6-12 months of LEN and who were RBC-TI and had achieved a CCyR (20)(21)(22).…”
Section: Introductionmentioning
confidence: 92%